2020
DOI: 10.1101/2020.06.19.158717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No evidence of coronaviruses or other potentially zoonotic viruses in Sunda pangolins (Manis javanica) entering the wildlife trade via Malaysia

Abstract: The legal and illegal trade in wildlife for food, medicine and other products is a globally significant threat to biodiversity that is also responsible for the emergence of pathogens that threaten human and livestock health and our global economy. Trade in wildlife likely played a role in the origin of COVID-19, and viruses closely related to SARS-CoV-2 have been identified in bats and pangolins, both traded widely. To investigate the possible role of pangolins as a source of potential zoonoses, we collected t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
(36 reference statements)
1
18
0
1
Order By: Relevance
“…Possibly due to selective pressure, the SARS-CoV-2 RBD, after evolving in horseshoe bats, has evolved further in a non-bat intermediate animal species before its zoonotic transfer to humans. In this regard, it is interesting to note that the SARS CoV-2 RBD is very similar to the one found in the SARS-related β-CoVs of Malayan pangolin [45][46][47][48], an endangered mammalian species. The viral sequences were found in archived samples of pangolins, who, similar to COVID-19 patients, had exhibited clinical symptoms such as cough and shortness of breath [46][47][48].…”
Section: Sars-cov-2 Interspecies Infectionssupporting
confidence: 58%
See 1 more Smart Citation
“…Possibly due to selective pressure, the SARS-CoV-2 RBD, after evolving in horseshoe bats, has evolved further in a non-bat intermediate animal species before its zoonotic transfer to humans. In this regard, it is interesting to note that the SARS CoV-2 RBD is very similar to the one found in the SARS-related β-CoVs of Malayan pangolin [45][46][47][48], an endangered mammalian species. The viral sequences were found in archived samples of pangolins, who, similar to COVID-19 patients, had exhibited clinical symptoms such as cough and shortness of breath [46][47][48].…”
Section: Sars-cov-2 Interspecies Infectionssupporting
confidence: 58%
“…Moreover, there was evidence of vertical transmission of the SARS-related β-CoVs in pangolins, suggesting virus circulation in this natural population [48]. However, testing of throat and rectal swabs from 334 pangolins sampled from the market's upstream supply chain, did not yield any positive PCR results for this CoV's nucleic acid sequences [46], suggesting that positive samples from pangolins in the market may have resulted from exposure to infected humans, wildlife or other animals. Thus, the existing evidence does not conclusively support the hypothesis that RaTG13 or pangolin β-CoV is the immediate parental virus of SARS-CoV-2.…”
Section: Sars-cov-2 Interspecies Infectionsmentioning
confidence: 97%
“…In addition, a recent study that investigated the possible role of pangolins as a source of potential zoonoses further exonerates the small mammal as potential intermediate host of COVID-19 47 . Throat and rectal swabs were collected from 334 Sunda pangolins (Manis javanica) confiscated and rescued from the wild in Peninsular Malaysia, and Sabah between August 2009 and March 2019 47 . No sample yielded a positive PCR result for any of the targeted viral families-Coronaviridae, Filoviridae, Flaviviridae, Orthomyxoviridae, and Paramyxoviridae 47 .…”
Section: Civet Cat and Pangolin: The Unlikely Scapegoats Of The Two Ementioning
confidence: 99%
“…Throat and rectal swabs were collected from 334 Sunda pangolins (Manis javanica) confiscated and rescued from the wild in Peninsular Malaysia, and Sabah between August 2009 and March 2019 47 . No sample yielded a positive PCR result for any of the targeted viral families-Coronaviridae, Filoviridae, Flaviviridae, Orthomyxoviridae, and Paramyxoviridae 47 . The authors suggested that the lack of coronavirus detection in their samples might suggest that the previous detection of the virus in these animal species could reflect their exposure to infected humans, wildlife, or other animals within the wildlife trade network 47 .…”
Section: Civet Cat and Pangolin: The Unlikely Scapegoats Of The Two Ementioning
confidence: 99%
“…The authors hypothesized that pangolins were an incidental host of coronaviruses potentially due to exposure to infected humans and other smuggled animals. 8 In the scenario where only two batches of smuggled pangolins possess these SARS-like CoVs, the CoVs could have come from other species held in captivity given the potentially broad host tropism of the related SARS-CoV-2 spike 912 and the fact that each of the two groups of smuggled pangolins carried a single CoV strain. For instance, a Hong Kong smuggling bust in 2014 discovered 40 boxes of pangolin and masked palm civet meat 13 (palm civets were an intermediate host of SARS-CoV, 2002-2004).…”
mentioning
confidence: 99%